PRINCIPALS’ COMPETENCIES AND TEACHERS’ JOB SATISFACTION AT DON BOSCO SCHOOLS UNDER THE CENTRAL FOUNDATION IN MANADO: BASIS FOR ENHANCEMENT PROGRAM FOR SCHOOL PRINCIPALS - Bogor Lumbanraja; Jontra Jusat Pangaribuan (English Lecturers and Teachers Association (ELTA), 2022)
This research is designed to determine the correlation between principals’ competencies and teachers’ job satisfaction at Selected Private Schools in Manado as input for Enhancement Programs. The principals’ competencies consisting of three aspects namely (1) Conceptual Competencies, (2) Technical Competencies, and (3) Human Relation Competencies. Meanwhile, the teachers’ job satisfaction was measured in terms of the following aspects: (1) Pay, (2) Promotion, (3) Supervision, (4) Fringe Benefits, (5) Contingent Rewards, (6) Operating Conditions, (7) Coworkers, (8) Nature of Work, and (9) Communication. The research was conducted using descriptive/correlational design; and Pearson Product Moment Correlation (Pearson r) to examine the correlation between identified variables. The results of the Pearson Correlation showed that most of the Principals’ Competencies are correlated with Job Satisfaction variables. Over-all, there is a positive significant correlation (r=0.364, p-value<0.05) between principal’s competencies and job satisfaction of teachers. The correlation can be interpreted as Moderate Relationship. The significant correlation between principals’ competencies and teachers’ job satisfaction implies that school principal should maintain and even increase their competencies if they want teachers to continue being satisfied with their job. Based on a reasonable output of this study, the researcher proposed a training program to enhance competencies of principals of Don Bosco Schools under the central fundation in Manado – Indonesia. Keywords: principals, conceptual competencies, technical competencies, human relation competencies, teachers, job satisfaction